Low‐Dose naltrexone restored TRPM3 ion channel function in natural killer cells from long COVID patients - Sasso, Etianne Martini; Eaton-Fitch, Natalie; Smith, Peter; Muraki, Katsuhiko; Marshall-Gradisnik, Sonya (Frontiers in Molecular Biosciences, 2025)
IntroductionLong COVID is a multisystemic condition that includes neurocognitive, immunological, gastrointestinal, and cardiovascular manifestations, independent of the severity or duration of the acute SARS-CoV-2 infection. Dysfunctional Transient Receptor Potential Melastatin 3 (TRPM3) ion channels are associated with the pathophysiology of long COVID due to reduced calcium (Ca2+) influx, negatively impacting cellular processes in diverse systems. Accumulating evidence suggests the potential therapeutic benefits of low-dose naltrexone (LDN) for people suffering from long COVID. Our study aimed to investigate the efficacy of LDN in restoring TRPM3 ion channel function in natural killer (NK) cells from long COVID patients.MethodsNK cells were isolated from nine individuals with long COVID, nine healthy controls, and nine individuals with long COVID who were administered LDN (3–4.5 mg/day). Electrophysiological experiments were conducted to assess TRPM3 ion channel functions modulated by pregnenolone sulfate (PregS) and ononetin.ResultsThe findings from this current research are the first to demonstrate that long COVID patients treated with LDN have restored TRPM3 ion channel function and validate previous reports of TRPM3 ion channel dysfunction in NK cells from individuals with long COVID not on treatment. There was no significant difference in TRPM3 currents between long COVID patients treated with LDN and healthy controls (HC), in either PregS-induced current amplitude (p > 0.9999) or resistance to ononetin (p > 0.9999).DiscussionOverall, our findings support LDN as a potentially beneficial treatment for long COVID patients by restoring TRPM3 ion channel function and reestablishing adequate Ca2+ influx necessary for homeostatic cellular processes.